2020
DOI: 10.1161/atvbaha.119.313137
|View full text |Cite
|
Sign up to set email alerts
|

IL (Interleukin)-6 Contributes to Deep Vein Thrombosis and Is Negatively Regulated by miR-338-5p

Abstract: Objective: Deep venous thrombosis (DVT), one of the most common venous thromboembolic disorders, is closely linked with pulmonary embolism and post-thrombotic syndrome, both of which have a high mortality. However, the factors that trigger DVT formation are still largely unknown. Elevated expression of IL (interleukin)-6—an important inflammatory cytokine—has been linked with DVT formation. However, the molecular mechanisms leading to the elevated IL-6 in DVT remain unclear. Here, we proposed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 52 publications
4
86
1
1
Order By: Relevance
“…has demonstrated the increase risk of deep vein thrombosis with tumor derived IL-6 in the mouse model of ovarian cancer via the induction of hepatic thrombopoietin, promoting thrombus formation [12]. Moreover, IL-6 has been reported to contribute to deep vein thrombosis by dysregulation of miR-338-5p expression [16].…”
Section: Discussionmentioning
confidence: 99%
“…has demonstrated the increase risk of deep vein thrombosis with tumor derived IL-6 in the mouse model of ovarian cancer via the induction of hepatic thrombopoietin, promoting thrombus formation [12]. Moreover, IL-6 has been reported to contribute to deep vein thrombosis by dysregulation of miR-338-5p expression [16].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with complicated appendicitis were reported to have higher plasma IL-6 level than those with simple appendicitis [11]. Elevated IL-6 might have induced DVT [12] in those patients. Further study is needed to confirm this theory.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al (2020) [52] demonstrated that the expression level of miR-103a-3p was downregulated not only in patients with acute DVT (n = 81) versus healthy controls (n = 20) but also in a mouse model of DVT (IVC stenosis model). Zhang et al (2020) [53] demonstrated that the expression of miR-338-5p was substantially downregulated in peripheral blood mononuclear cells of DVT patients (n = 36) in comparison to healthy controls (n = 36). Consistent with the findings in DVT patients, the expression of miR-338-5p was significantly lower in a mouse model of DVT (IVC stenosis model) versus control mice [53].…”
Section: Epidemiological Studies: Mirnas and Venous Thromboembolismmentioning
confidence: 99%
“…Zhang et al (2020) [53] demonstrated that the expression of miR-338-5p was substantially downregulated in peripheral blood mononuclear cells of DVT patients (n = 36) in comparison to healthy controls (n = 36). Consistent with the findings in DVT patients, the expression of miR-338-5p was significantly lower in a mouse model of DVT (IVC stenosis model) versus control mice [53].…”
Section: Epidemiological Studies: Mirnas and Venous Thromboembolismmentioning
confidence: 99%
See 1 more Smart Citation